Formation of a conceptual approach to the creation of an expert system for the identification of the processes of intellectual activity - Serdiuk, Olga (Eastern-European Journal of Enterprise Technologies, 2015)
Reliable identification of the level of intellectual activity, analysis of the development dynamics and diagnostics of intellectual processes require the creation of a new class of expert systems. One of the main points that should be taken into account in creating expert systems and in the works aimed at identifying the processes of intellectual activity, is the evaluation not of intelligence, in general, as a single complex system, but its individual processes. Only in this case, it is possible to undertake an in-depth analysis of the current state and development dynamics of the processes of intellectual systems, gain access to the possibility of implementing an effective diagnostics of possible problems and identify ways to resolve them. As it was found in the research, a prerequisite for the implementation of these approaches is the use of system grounded evaluation criterion. Such criterion should be consistent with the criterion of the efficiency of open systems. The evaluation criterion, the choice of which was done in this paper, allows to take into account the complexity level, the deviation of response from the standard and time of the test or task solution. Using the system grounded evaluation index allowed to propose a unified methodology to characterize both the dynamics of the processes and the maximum achievable level with an unlimited range of its change. Use of the trend dependence, approximating the dynamic series allows to obtain additional opportunities to assess the degree of concentration, and other influencing factors in the form of standard deviation indicator. Also, the proposed criterion provides the possibility of evaluating the entire process as a sequence of evaluation operations, which potentially allows to optimize the parameters of operations that are set prior to carrying out the experiments.